Aesthetic Periodontal Enhancement Through Parallel Technique Frenectomy in Orthodontic Patient: A Clinical Case Report - Marapandi Cakra; Kwartarini Murdiastuti; Dharmmesti Anindita Wijayanti; Dayanara Amarita Merukh; Septi Handayani (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: A high maxillary labial frenum with midline diastema can compromise both dental aesthetics and periodontal health. Frenectomy using a parallel incision technique has been proposed as a minimally invasive approach to promote optimal soft tissue architecture while supporting orthodontic stability. Case: A 22-year-old female patient presented with a high-attached maxillary labial frenum resulting in midline diastema during ongoing orthodontic treatment. Case Management: A parallel technique frenectomy was performed before diastema closure to improve the width of attached gingiva and enhance soft tissue aesthetics. Clinical follow-up was carried out at 8, 13, and 46 days post-surgery, assessing attached gingiva width, gingival margin level, and papilla fill. Discussions: Progressive healing demonstrated increased attached gingiva width, improved gingival margin level, and enhanced interdental papilla fill. Soft tissue contour appeared more harmonious with midline alignment, contributing to improved aesthetic outcomes and periodontal stability before diastema closure. Conclusion: Parallel technique frenectomy can effectively enhance the aesthetic and periodontal condition in orthodontic patients with aberrant labial frenum attachment. Early surgical intervention before diastema closure may aid in achieving stable soft tissue architecture and optimizing future orthodontic outcomes.